Case Report: The management of hemorrhagic shock of different origins by target-controlled coagulation and extracorporeal organ support (continuous renal replacement therapy) - Pertich, Ákos; Lovas, András (Frontiers in Anesthesiology, 2024)
Introduction Trauma-related severe bleeding and peripartum hemorrhage complicated by shock state is challenging for acute care physicians. Management steps relating to each other include damage control surgery, maintenance of optimal clotting preconditions, point-of-care and targeted supplementation of coagulation factors, control of hyperfibrinolysis, and supplementation of thrombocytes. Extensive tissue damage and surgical management of bleeding activate the proinflammatory process, leading to a dysregulated immune response. The originating systemic inflammation produces further damage, harmfully altering clot formation through the activation of immunothrombosis. Clinical findings The case report presents one obstetric, massive bleeding patient and one politraumatized patient with severe hemorrhage. Both underwent extended surgery regarding bleeding control intervention. Interventions and outcome Elimination of coagulation disorder was driven by point-of-care viscoelastometry and targeted clotting factor supplementation. Continuous renal replacement therapy and the hemadsorption technique augmented the well-established, up-to-date recommendations-guided care throughout the treatment line. The patients could leave the intensive care unit 4 and 8 days following the initial injury. Conclusion Prompt administration of extracorporeal organ support enhanced the recovery from hemorrhagic shock.